Optimal FM Strategy for Commercial Office Buildings Using Fuzzy Synthetic Evaluation - Yoon, Jong Han; Cha, Hee Sung (Journal of Performance of Constructed Facilities, 2018)
For owners of aged buildings, considerable attention needs to be devoted to efficient facility management (FM) to extend building life and achieve life-cycle cost savings. The fundamental step in this is to identify the level of FM performance. Few studies have focused on the quantitative investigation of FM performance, and there has been minimal research on the methodology required to arrive at the optimal strategy. The purpose of this study is to present a systematic algorithm that allows FM practitioners to evaluate their performance in an objective manner. In addition, the authors have formulated a FM performance evaluation index in conjunction with the fuzzy synthetic evaluation method. The framework for this evaluation includes 12 critical success factors and 18 key performance indicators according to 4 balanced scorecard perspectives. A case study on a commercial office building was conducted to demonstrate the effectiveness and validity of the proposed methodology. The results reveal an optimal FM strategy for the building recommended using the novel algorithm, and its effectiveness is validated by FM experts. The proposed method will allow industry practitioners to quantitatively evaluate FM performance and make better decisions in selecting the optimal management strategy. Furthermore, the findings can advance the body of knowledge on building performance evaluation in view of quantitative metrics development.
Keywords: Building performance evaluation; Critical success factor; Facility management; Fuzzy synthetic evaluation; Key performance indicators; Optimal management strategy; Performance evaluation index; Quantitative investigation; Commercial office building; Decision making; Facility management strategy; Fuzzy synthetic evaluation; Quantitative analysis